Revisiting 30 years of biofunctionalization and surface chemistry of inorganic nanoparticles for nanomedicine - Conde, João (2014)
FP7-PEOPLE-2013-IOF, Project no. 626386 PEst-OE/SAU/U10009/2011-14 MAT2011-26851-C02-01